2019
DOI: 10.5194/hess-23-3885-2019
|View full text |Cite
|
Sign up to set email alerts
|

Local and remote moisture sources for extreme precipitation: a study of the two catastrophic 1982 western Mediterranean episodes

Abstract: Abstract. Floods and flash floods are frequent in the south of Europe resulting from heavy rainfall events that often produce more than 200 mm in less than 24 h. Even though the meteorological conditions favourable for these situations have been widely studied, there is a lingering question that still arises: what humidity sources could explain so much precipitation? To answer this question, the regional atmospheric Weather Research and Forecasting (WRF) model with a recently implemented moisture tagging capab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 39 publications
1
17
1
Order By: Relevance
“…In turn, the synoptic-scale circulation will give some types of weather that may favour the development of intense rains, which are the main cause of floods in the Mediterranean, such as the presence of synoptic or mesoscale lows Llasat, 2017, Jansà et al, 2014). These results are consistent with the studies that are currently being carried out to find the sources of water vapour that feed the intense rains in the Mediterranean and that demonstrate the notable role of sources of Atlantic origin, against the existing perception that most came from the Mediterranean (Insua-Costa et al, 2019). In this context, the latest flood episodes that have affected the Spanish Mediterranean coast would be a call for reflection, given the influence that the Greenland thaw has on large-scale climate variability over the Mediterranean basin, partially associated with circulation patterns such as the Arctic Oscillation (AO) and the North Atlantic Oscillation (NAO), which control part of the moisture fluxes over the western and eastern Mediterranean basins (Tramblay and Hertig, 2018).…”
Section: Secular Changessupporting
confidence: 91%
See 1 more Smart Citation
“…In turn, the synoptic-scale circulation will give some types of weather that may favour the development of intense rains, which are the main cause of floods in the Mediterranean, such as the presence of synoptic or mesoscale lows Llasat, 2017, Jansà et al, 2014). These results are consistent with the studies that are currently being carried out to find the sources of water vapour that feed the intense rains in the Mediterranean and that demonstrate the notable role of sources of Atlantic origin, against the existing perception that most came from the Mediterranean (Insua-Costa et al, 2019). In this context, the latest flood episodes that have affected the Spanish Mediterranean coast would be a call for reflection, given the influence that the Greenland thaw has on large-scale climate variability over the Mediterranean basin, partially associated with circulation patterns such as the Arctic Oscillation (AO) and the North Atlantic Oscillation (NAO), which control part of the moisture fluxes over the western and eastern Mediterranean basins (Tramblay and Hertig, 2018).…”
Section: Secular Changessupporting
confidence: 91%
“…It is in an area where subtropical and polar air masses can converge, giving rise to severe weather and heavy rainfall. For instance, Insua-Costa et al (2019) have demonstrated that the precipitable water mass during the October and November 1982 floods were mainly from the subtropical Atlantic and Western Mediterranean. In addition, the Mediterranean is a warm and almost closed sea, surrounded by an orography characterized by a notable mountainous relief, which favours cyclogenesis and an air mass with high humidity, instability and latent energy, with the consequent development of adverse weather events such as flash floods or strong wind storms (Jansà et al, 2014).…”
Section: Study Areamentioning
confidence: 99%
“…The contribution from the rest of the source regions exhibits strong intra-seasonal variations during summer and fall over the eastern parts of the ML. The variations in moisture transport at sub-seasonal timescales has been noted in earlier studies where different events within the same season were driven by moisture contribution from distinct sources (Insua-Costa et al 2019). Nonetheless, it is important to note that despite the monthly-scale variability in the moisture transport from individual sources, the order of moisture contribution from major moisture sources, identified using seasonal means, does not change.…”
Section: Major Moisture Sources At Seasonal Scalementioning
confidence: 57%
“…Torrential rainfall during this synoptic situation is concentrated on the southern slope, as shown in Figure 7, as a result of this important moisture that was advected from subtropical origin. In fact, Insua-Costa et al [56] recently showed that moisture advected via an atmospheric river from the tropical and subtropical Atlantic played a major role in a well-known case of this type, the November 1982 flood event. In addition, this type of episode has aroused interest in studying the physical mechanisms of high precipitation events related to this synoptic pattern in the eastern Pyrenees [10,11].…”
Section: Large-scale Attribution Of Torrential Eventsmentioning
confidence: 99%